2011
DOI: 10.1161/atvbaha.110.216473
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Erg Inhibits Vascular Inflammation by Repressing NF-κB Activation and Proinflammatory Gene Expression in Endothelial Cells

Abstract: We have identified a novel physiological anti-inflammatory pathway under the control of the transcription factor Erg; this pathway inhibits NF-κB-dependent transcription and TNF-α-induced inflammation in vivo. These results suggest a novel approach to anti-inflammatory therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 40 publications
7
110
0
Order By: Relevance
“…Erg is a member of the ETS family of transcription factors, which is mainly expressed by endothelial cells (34,35). Erg maintains endothelial cells in a non-activated state by constitutively repressing NF-B activity and ICAM-1 expression after TNF␣ stimulation (36,37). Erg also reduces the expression of inflammatory cytokines such as interleukin-8 (38), and its down-regulation leads to spontaneous neutrophil attachment to nonstimulated endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Erg is a member of the ETS family of transcription factors, which is mainly expressed by endothelial cells (34,35). Erg maintains endothelial cells in a non-activated state by constitutively repressing NF-B activity and ICAM-1 expression after TNF␣ stimulation (36,37). Erg also reduces the expression of inflammatory cytokines such as interleukin-8 (38), and its down-regulation leads to spontaneous neutrophil attachment to nonstimulated endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…ERG is a key regulator of cell proliferation and differentiation, and angiogenesis. 39 Regarding the top 10 overexpressed genes, RPL7A is a ribosomal protein and an altered pattern of RPL7 expression has been described in colorectal carcinoma. 40 …”
Section: Genes Differentially Expressed Between Mgus and Smmmentioning
confidence: 99%
“…16,17 It is also constitutively expressed in normal endothelial cells and regulates angiogenesis and endothelial apoptosis. [18][19][20] Several studies have shown anti-ERG antibody useful for prostate carcinoma, metastatic and primary, and prostatic intraepithelial neoplasias. [10][11][12]21,22 The detection of ERG is highly correlated with both ERG rearrangement by fluorescence in-situ hybridization and with ERG mRNA overexpression.…”
mentioning
confidence: 99%